FAKTOR–FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cittadila Prila Kartini, 14.05.52.0163; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the effect of dividend policy, firm size, managerial ownership, institutional ownership, and profitability to debt policy at manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2013-2015. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the year 2013-2015. Sampling technique in this research is purposive sampling. The data obtained were analyzed by using multiple linear  regression analysis. Hypothesis testing results can be concluded that the dividend policy does not affect the debt policy. Company size has a positive effect on debt policy. Managerial ownership has no effect on debt policy. Institutional ownership has no effect on debt policy. Profitability has a negative effect on debt policy. Keywords: Dividend Policy, Firm Size, Managerial Ownership, Institutional Ownership and Debt Policy